Indonesia social progress: the role of access to basic education in escaping from poverty trap - Haidir, Andi Ahmad; Setyari, Ni Putu Wiwin (Jurnal Ekonomi & Studi Pembangunan, 2023)
As Indonesia enters the post-pandemic world, it faces high uncertainty, especially in terms of access to basic education. According to the Central Bureau of Statistics (BPS), the education sector grew by 0.42%, the second-lowest of all sectors. However, its contribution to economic growth was the highest at 3.02%, surpassing six other sectors with higher growth. Despite this potential, access to education remains low. This research aimed to examine the role of access to basic education in alleviating poverty in Indonesia with the social progress perspective. The analytical framework for this research was based on the approach of Amartya Sen, who view poverty as capability deprivation. This research used educational data from BPS in 2022 from 34 provinces in Indonesia. The data were used to construct a social progress index, which measures access to basic education. The index was developed using nine indicators, namely primary school enrolment, secondary school attainment, population with no schooling, gender parity in secondary attainment, teacher-student ratio, teacher qualification, school proportion, classroom condition, and availability of water and sanitation. The index of access to basic education was then regressed along with other variables that are relevant to capability deprivation, as proposed by Hick. These variables include the Happiness Index, Democracy Index, Level of Health Inequality, and Crime Rate. The results indicated that all these variables had a significant impact on the poverty level. Among all the variables, access to basic education demonstrated the greatest influence compared to the other four variables. This suggests that access to basic education plays a critical role in poverty reduction. The research findings highlight the potential of using the Social Progress Index as a comprehensive metric for development, which offers a more inclusive understanding of progress. This index encompasses a broad framework comprising 60 indicators, and does not rely solely on GDP measurements.